Efficient Lightweight Concrete Based on Porous Aggregates - Rizayev B. Sh., Kholmirzayev S. A., Ahmedov I. G’.; Sharopov B. Kh. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article discusses the experience of using lightweight aggregates Due to the difficulty of producing expensive aggregates, this problem makes us turn to the use of new types of porous aggregates on local raw materials and coal waste in lightweight concretes